2020
DOI: 10.1507/endocrj.ej19-0498
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of captopril challenge test can predict results of other confirmatory tests for primary aldosteronism and propose the next test to be done

Abstract: In Japan, primary aldosteronism (PA) is diagnosed if any one of the captopril challenge test (CCT), saline infusion test (SIT), furosemide-upright test (FUP), and oral salt-loading test (OST) is positive. The present study aimed to investigate if parameters of CCT, the safest confirmatory test, could predict decisions of other tests and propose the next test to diagnose PA in CCT-negative patients. In a cross-sectional design, 142 patients, who were referred to our hospital for the scrutiny of PA and underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Because patients highly suspected of PA had been preferentially referred to our center, the prevalence of PA among our patients should be much higher than that among patients with hypertension in general practice. Actually, we previously reported that 128 (90.1%) of 142 patients, who received PA confirmatory tests for the scrutiny of PA in our center from April 2012 to December 2017, were PA patients [ 28 ]. On the other hand, patients whose PAC or PRA values had been measured in the scrutiny of adrenal incidentaloma, adrenal insufficiency, and renovascular hypertension were also included in the present study ( Fig 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because patients highly suspected of PA had been preferentially referred to our center, the prevalence of PA among our patients should be much higher than that among patients with hypertension in general practice. Actually, we previously reported that 128 (90.1%) of 142 patients, who received PA confirmatory tests for the scrutiny of PA in our center from April 2012 to December 2017, were PA patients [ 28 ]. On the other hand, patients whose PAC or PRA values had been measured in the scrutiny of adrenal incidentaloma, adrenal insufficiency, and renovascular hypertension were also included in the present study ( Fig 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal cutoff value of basal CLEIA-ARR to detect PA patients was previously reported to be >6 ng/dL over pg/mL, where PA was diagnosed only by CCT [ 15 ]. Because 77% of CCT-negative patients were diagnosed with PA by SIT or FUP in our previous report [ 28 ], the cutoff value should be decreased to pick up CCT-negative PA patients. If PA had been diagnosed only by CCT in the present study, ten of 44 PA patients would have been diagnosed with non-PA and the optimal cutoff of basal CLEIA-ARR to detect PA would have increased to >3.47 ng/dL over pg/mL (Panel A of S3 Fig , S13 Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Variables derived from CCT included aldosterone concentration, aldosterone concentration inhibition rate, and ARR. Among them, aldosterone concentration has the best diagnostic performance and thus recommended ( 10 12 ). However, there is lack of consensus on the timing of blood sampling after captopril challenge ( 5 , 6 , 13 – 15 ).…”
Section: Introductionmentioning
confidence: 99%